2009
DOI: 10.1016/j.paid.2008.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Handedness and behavioural inhibition: Left-handed females show most inhibition as measured by BIS/BAS self-report

Abstract: This study investigated the relationship between handedness, gender and behavioural approach and inhibition using Carver and White's (1994) BIS/BAS Scale. 112 participants took part: 46 left-handers and 66 right-handers. All participants completed Peters' (1998) handedness questionnaire followed by the self-report BIS/BAS Scale. Significant effects of both handedness and gender on the BIS scores were found, with left-handers and females scoring significantly higher on inhibition. BIS scores were reexamined to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
38
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 31 publications
7
38
1
Order By: Relevance
“…(2015). Handedness and behavioural inhibition system/behavioural activation system (BIS/BAS) scores: A replication and extension of Wright, Hardie, and Wilson (2009). Laterality, 20(5), pp.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…(2015). Handedness and behavioural inhibition system/behavioural activation system (BIS/BAS) scores: A replication and extension of Wright, Hardie, and Wilson (2009). Laterality, 20(5), pp.…”
mentioning
confidence: 99%
“…This study was criticised by Hicks & Pellegrini (1978) Dillon (1989) reported a significant correlation among 34 male but not 44 female college students between scores on a questionnaire assessing students' worries and scores on a General Laterality Scale. Using the Edinburgh Handedness Inventory (EHI), Merkelbach, de Ruiter and Olff (1989) compared the handedness of 77 anxiety disorder patients with handedness in a healthy control 6 group and found no evidence of a relationship between left-handedness and clinically diagnosed anxiety.In a recent study Lyle, Chapman and Hatton (2013) Previously they had found (Wright, Hardie & Wilson, 2009) that left-handers reported themselves to have higher BIS scores than right-handers on a questionnaire developed by Carver and White (1994) to measure constructs proposed by Gray's (1982) theory of two independent neural systems -the behavioural inhibition system (BIS) and the behavioural approach system (BAS). Subsequently these two systems, originally conceived of as underlying anxiety and avoidance on the one hand (BIS) and impulsivity or approach behaviour on the other (BAS), were modified and extended by the introduction of a third system representing a fight-flight-freeze system (FFFS) relating to an…”
mentioning
confidence: 99%
See 3 more Smart Citations